2013
DOI: 10.1558/cj.v23i2.281-307
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of the Effects of a Story-based Video Instructional Package Versus a Text-based Instructional Package in the Intermediate-level Foreign Language Classroom

Abstract: This study compared a story-based video instructional package, with a feature-length film as its focus, to a text-based program. It explored the effectiveness of each approach to enhance the listening and grammar performances of intermediate-level college French students. Twenty-seven students at two institutions participated. A pretest-posttest design assessed long-term gains in listening performance and grammar performance. Results indicated that students significantly improved their listening skills and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 16 publications
5
36
0
2
Order By: Relevance
“…interruptions, unrelated information, or background noise) [29]. One approach to address bounds on cognition is by the use of richer media [30]. Videos, for example, are stored in the episodic memory [47] rather than semantic [35] as coding is based in context rather than content [46].…”
Section: Background and Related Workmentioning
confidence: 99%
“…interruptions, unrelated information, or background noise) [29]. One approach to address bounds on cognition is by the use of richer media [30]. Videos, for example, are stored in the episodic memory [47] rather than semantic [35] as coding is based in context rather than content [46].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Research has shown that videos can lead to richer comprehension over text 13 . We measure comprehension of the videos by participants as follows: (1) they should be able to identify the risk; (2) they should be able to identify the attack vector; (3) they should be able to identify the potential consequences of the risk; (4) they should be able to suggest strategies to avoid or mitigate the risk.…”
Section: Comprehension: Video Vs Textmentioning
confidence: 99%
“…Furthermore, previous studies suggest that language learners showed positive attitudes towards online learning and the use of web-based materials in language learning due to their availability, variety, privacy, authenticity, interesting presentation, novelty, convenience, accessibility and rich cultural content (Coryell & Chlup, 2007;Felix, 2001aFelix, , 2001bFelix, , 2002Ma, 2007;Murday, et al, 2008;Nah, 2008;Suarcaya, 2011;Wagener, 2006). The flexibility and abundance of the online learning environment make it a suitable environment for independent learning activities (Meskill & Anthony, 2010), and for learners of intermediate level of English proficiency who are considered ready to use the technology and explore the content (Harlow & Muyskens, 1994;Herron, York, Corrie, & Cole, 2006).…”
Section: The Potential and Challenges Of Web-based Language Learningmentioning
confidence: 99%
“… They promote listening skills development and media literacy skills of analysis, evaluation, and communication (Gruba, 2006); and  They are appropriate for intermediate levels of L2 listening proficiency (Guichon & McLornan, 2008;Harlow & Muyskens, 1994;Herron, et al, 2006).…”
Section: Benefits and Drawbacks Of Language Learning Websites For Thementioning
confidence: 99%
See 1 more Smart Citation